One scientist-one technology-one village programme: An innovative model for dissemination of farm technology - Choudhary, Anil K.; Thakur, S.K.; Yadav, D.S.; Rahi, Shakuntla; Sood, Pankaj; Chauhan, Kalpna; Singh, Amar; Dardi, M.S. (Annals of Agricultural Research, 2016)
Agriculture, horticulture and livestock rearing are integral part of hill farming in Himachal Pradesh in general and Mandi district in particular. Rainfed farming and lack of awareness about improved farm technology are major constraints in the district where majority of farmers have poor socioeconomic status practicing poor crop management with low crop productivity and profitability. This situation emphasized upon dissemination and adoption of farm technology through efficient and appropriate extension technologies to the hill farmers. The past experience of technology dissemination and adoption at slow pace with conventional extension approaches suggested for evolving innovative extension tools. Moreover, role of KVKs is crucial in present agrarian scenario to frame new innovative extension tools for knowledge upgradation for effective farm technology dissemination and adoption to benefit farmers. Thus, following past experiences of technology transfer model under IFFCO-KVK Collaborative Project executed by KVK Mandi and by other researchees in other parts of the globe; an innovative extension model 'One Scientist-One TechnologyOne Village' involving interventions like KVK expertise flow to farmers, farmer-farmer based extension system, model farm development, 'on-farm' experimentation, field demonstrations, trainings, field days, field conventions and visits, individual consultations and literature flow etc.; was developed at KVK, Mandi (HP) with the objective of technology dissemination at village level utilizing particular KVK expertise in holistic manner. This paper deals with the discussion on evolution and principles of this innovative extension model and how it is useful to the hill farmers in dissemination and adoption of farm technology to boost their productivity and transform their hill production systems into highly remunerative systems using available farm resources and need based and location-specific, socially acceptable and technically sound technologies to generate better farm gains and livelihoods on sustainable basis.